Situation Report: Czechoslovakia, 25 September 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Leader Gustav Husak in Helsinki The Svit Works 80th Anniversary The New Dramatic Season